Grupa pułkowników jako zaplecze polityczne rządów autorytarnych w latach 1926–1939 - Piotrowski, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The authority of Józef Piłsudski in Poland was mainly based on a group of his close associates from the army. They supported the idea of strong authority operating on the edge of the law in order to build a strong, resistant country. They transferred the army methods to public life. For the sake of effectiveness in their political struggle they were ready to use even brutal methods. Nowadays, we are reserved as far as authoritarian political solutions are concerned. Nevertheless, in order to judge them objectively, they must be seen on the background of European political reality of the time when such political conceptions were quite common. The Colonels’ Group preferred to base the political system on reliable elite corps instead of building a mass political movement. They found a small determined group able to act for the sake of independence to be a superior form of organization. Fighting for the independence, which was their fundamental idea, they frequently challenged the basic democratic principles. The democrats perceived them as blind followers aiming to eliminate political parties from public life. They perceived themselves as creators and guards of the independent country. After the death of Marshal Piłsudski they had to pay a high price for all the great political roles of Prime Ministers, ministers, members of parliament they played during his lifetime. Many of them were killed by the invaders and some by Polish communists after 1945.
Keywords: II Rzeczpospolita; Piłsudski, Józef (1867-1935); autorytaryzm w II Rzeczypospolitej; "grupa pułkowników"